Anti-inflammatory lipoxin A 4 is an endogenous allosteric enhancer of CB 1 cannabinoid receptor - Fabrício A. Pamplona; Juliano Ferreira; Octávio Menezes de Lima; Filipe Silveira Duarte; Allisson Freire Bento; Stefânia Forner; Jardel Gomes Villarinho; Luigi Bellocchio; Carsten T. Wotjak; Raissa Lerner; Krisztina Monory; Beat Lutz; et al. (2012)
Allosteric modulation of G-protein–coupled receptors represents a key goal of current pharmacology. In particular, endogenous allosteric modulators might represent important targets of interventions aimed at maximizing therapeutic efficacy and reducing side effects of drugs. Here we show that the anti-inflammatory lipid lipoxin A 4 is an endogenous allosteric enhancer of the CB 1 cannabinoid receptor. Lipoxin A 4 was detected in brain tissues, did not compete for the orthosteric binding site of the CB 1 receptor (vs. 3 H-SR141716A), and did not alter endocannabinoid metabolism (as opposed to URB597 and MAFP), but it enhanced affinity of anandamide at the CB1 receptor, thereby potentiating the effects of this endocannabinoid both in vitro and in vivo. In addition, lipoxin A 4 displayed a CB 1 receptor-dependent protective effect against β-amyloid (1–40)-induced spatial memory impairment in mice. The discovery of lipoxins as a class of endogenous allosteric modulators of CB 1 receptors may foster the therapeutic exploitation of the endocannabinoid system, in particular for the treatment of neurodegenerative disorders.